A Study on Cohesive Devices Used in EFL Students’ Descriptive Paragraph: Studi tentang Peranti Kohesif yang Digunakan dalam Paragraf Deskriptif Mahasiswa EFL - Haidari, Sultan Ali; Rasuli, Mohammad Hassan (Himpunan Sarjana Kesusastraan Indonesia (HISKI) Komisariat Kalimantan Timur, 2025)
This study investigated the degree to which EFL students utilize cohesive devices in their written work. Sixteen undergraduate students (10 female, 6 male) who had completed at least five semesters in the English Department participated in the research. Writing assignments were collected as data using a quantitative approach. Holliday and Hasan’s taxonomy was employed for data analysis. The analysis revealed that third-year English majors were unable to maintain a parallel use of various cohesive devices when writing English paragraphs. While they frequently utilized conjunctions and references, they rarely employed ellipses or substitutions in their descriptive paragraphs. This avoidance of substitution and ellipsis subsequently led them to overuse reference and conjunction adequately. The results also indicated that although the students understand the fundamental purpose of cohesive devices, they occasionally struggled with subtle usage and displayed a limited vocabulary of cohesive devices. Based on correctness and incorrectness, it was found that the majority of students successfully applied cohesive devices in their text; however, they still employed some cohesive devices incorrectly.